A Power Factor Corrected Bridgeless Type III Cuk Derived Converter fed BLDC Motor Drive - J. Pearly Catherine; R. Balamurugan (Indonesian Journal of Electrical Engineering and Computer Science, 2015)
This paper deals with the power factor correction in BLDC motor drive with different cuk derived converter topologies and the best one is simulated for power factor correction operation. Power quality issues is the major concern in the BLDC motor drive due to recommended limits of harmonics in the supply current. Conventionally the BLDC motors are powered with the help of diode bridge rectifiers which results in highly distorted supply current and poor power factor. So modification in converter topology is the research hotspot in recent years. Alternatively bridgeless converter topologies are used in place of diode bridge rectifiers (DBR). Among the bridgeless topologies cuk derived converters suited well for power factor correction. In this paper the different cuk topologies are investigated and the best one is simulated with the help of neuro-fuzzy controller in MATLAB/Simulink platform.DOI: http://dx.doi.org/10.11591/telkomnika.v14i3.7893